Reducing the Costs of Course Materials. Issue 2 (3rd April 2017) - Farb, Sharon E.; Glushko, Robert; Orfano, Stephanie; Smith, Kelly
ABSTRACT: The University of California, Los Angeles (UCLA) and University of Toronto (U of T) describe their respective library-driven programs to reduce the cost of course materials for students—the Affordable Course Materials Initiative (ACMI) at UCLA and the Zero-to-Low-Cost-Course Program (ZTLCC) at U of T. With the same goal of reducing costs by leveraging existing library resources, each library approaches that cost reduction differently. UCLA uses financial incentives to help drive faculty participation in reducing costs, whereas U of T works to reduce overlap in licensing costs while encouraging use of these already-paid-for resources. The following provides an overview of each program along with guidelines for implementing a similar program.